Eletrocoagulação como pós-tratamento do efluente de um tanque séptico e de um wetland construído de fluxo vertical - Goerck, Janaina (2018)
Domestic wastewater must be treated before being released into the environment, otherwise, the excessive contaminants amount may degrade the water quality of the receiving body causing problems to the environment and to the public health. An expanding unit process operation is the electrocoagulation, an electrochemical process where the coagulant is produced in situ through the application of a potential difference. The generated coagulant destabilizes the solution and aggregates with colloidal structures and suspended solids creating aggregates that are going to be removed by flotation promoting the effluent treatment. The aim of this study was to apply the electrocoagulation, under the same conditions during a period, as a post-treatment of an effluent from a secondary treatment by vertical flow constructed wetland (VFCW) and to evaluate the phosphorus, nitrogen, total coliforms, Escherichia coli, carbonaceous organic matter (COD), turbidity, apparent color, electrical conductivity removal, and to monitor pH and temperature. Together, it was applied the electrocoagulation in the primary effluent from a septic tank (ST), aiming to remove and monitor the same parameters and to examine the EC application viability as secondary treatment. The electrocoagulation reactors with aluminum electrodes were design in bench scale and the best experimental conditions found to the VFCW effluent was 1.3 A x 18 min (EC-WC) and to the ST effluent was 2.0 A x 12 min (EC-TS). During thirteen weeks the treatments were applied and the final average concentration of P-PO43-, N-NH4+, N-NO2-, N-NO3-, total coliforms, E. coli, COD, turbidity, apparent color, pH, EC, and temperature in the EC-WC were n.d. (non-detectable), 43.5 mg.L-1, 1.3 mg.L-1, 17.8 mg.L-1, 1.75x104 NMP.100 mL-1, 5.59x103 NMP.100 mL-1, 44.95 mg.L-1, 5.84 NTU, 62.4 uC, 8.8, 762.7 μS.cm-1, 23.5 ºC, respectively. To the EC-TS the results were n.d. (non-detectable), 63.9 mg.L-1, n.d., 0.1 mg.L-1, 3.75x104 NMP.100 mL-1, 1.03x104 NMP.100 mL-1, 81.77 mg.L-1, 5.65 NTU, 69.5 uC, 8.5, 868.2 μS.cm-1, 25 ºC, respectively. Both treatments, EC-WC and EC-TS showed high pollutants removal efficiency and final concentrations below released reference values established by Brazilian Law CONSEMA Resolution nº 355/2017, CONAMA Resolution nº 430/2011 and NBR 13.969/1997, except to the ammoniacal nitrogen, showing that EC can be used as post-treatment of ST and VFCW as well. Statistically, the treatments showed significant difference regarding nitrogen and the VFCW proved to be fundamental to the N-NH4+ removal and effluent generation with less polluting potential. Electrocoagulation with aluminum electrodes proved to be a promising unit process operation to the domestic wastewater treatment.